Fisheries and aquaculture by-products modulate growth, body composition, and omega-3 polyunsaturated fatty acid content in black soldier fly (Hermetia illucens) larvae - Rosaria Arena; Simona Manuguerra; Eleonora Curcuraci; Maria Cusimano; Daniela Lo Monaco; Calogero Di Bella; Andrea Santulli; Andrea Santulli; Concetta Maria Messina (Frontiers in Animal Science, 2023)
The black soldier fly (BSF) (Hermetia illucens L.) is one of the most promising species for the production of ingredients, mainly protein, useful for animal feed formulation, owing to its ability to convert organic waste into biomass with a high nutritional value. However, the low percentage of n-3 series polyunsaturated fatty acids (PUFAs) in its fatty acid profile is a limiting factor for the utilization of BSF in fish feed. Recent studies have highlighted that wastes derived from different agro-food value chains could affect the nutritional composition of BSF larvae, depending on the composition of the wastes used as larvae-growing substrate. Due to the significant amount of n-3 PUFA in marine products, both in edible produce and in by-products, in this study, different sources of fish by-products were included in experimental diets for BSF to evaluate the effect of its addition on the final nutritional profile of BSF pre-pupae. One control diet and five experimental diets were prepared to feed the BSF larvae: wheat bran as the control diet (diet B), bycatch from Mediterranean trawl fisheries (diet F), Parapenaeus longirostris processing by-products (diet S), aquaculture processing by-products (diet R), Thunnus albacares processing by-products (diet T), and Engraulis encrasicolus processing by-products (diet A). In this study, the effects of the different diets were analyzed on the growth, body composition, and fatty acid profile of BSF larvae and pre-pupae. The obtained results showed that the different experimental diets affected total lipids content and fatty acids composition, when compared with the control. A significant increase in eicosapentaenoic (EPA) and docosahexaenoic acid (DHA) in BSF larvae and pre-pupae fed with all fish by-products was observed when compared with those fed with diet B, in particular in larvae and pre-pupae fed with diet A, demonstrating that the utilization of fish processing by-products is a suitable solution for improving the nutritional value of insects as ingredients in aqua feeds. The reuse of marine by-products can contribute to the industry’s “zero waste” goal, increasing the sustainability of the fishery value chain and the formulation of new valuable products.